Inovasi Kurikulum Qur’an Hadis Berbasis Media Digital Quizizz dalam Implementasi Kurikulum Merdeka di MI Al-Huda Karangnongko - Hidayah Yanti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to analyze curriculum innovation in the Qur’an and Hadith subject within the implementation of the Merdeka Curriculum, focusing on the need for more interactive, contextual, and student-centered learning. This research addresses the limitations of conventional teaching methods that previously led to low student participation and understanding. Design/methods– This study employed a qualitative descriptive approach with a case study design. Data were collected through classroom observations, structured interviews, and documentation involving teachers and students. Data analysis followed the Miles, Huberman, and Saldana model, including data reduction, data display, and conclusion drawing. Data validity was ensured through member checking. Findings – The findings reveal that curriculum innovation was implemented through the integration of Quizizz as a digital learning medium in Qur’an and Hadith instruction. This approach significantly increased student participation and motivation, as evidenced by more active classroom engagement. Cognitively, students demonstrated improved understanding of the subject matter; affectively, they showed greater confidence and collaborative attitudes; and psychomotorically, their ability in religious practices, such as reciting and memorizing verses, improved. Furthermore, Quizizz facilitated efficient formative assessment by providing immediate feedback and measurable learning data. Despite challenges such as unstable internet connectivity and varying levels of teachers’ digital literacy, the innovation proved effective in enhancing the overall quality of learning.